Evaluation of serum levels of multiple cytokines and adhesion molecules in patients with newly diagnosed acute lymphoblastic leukemia using biochip array technology - Horacek, J.M.; Kupsa, T.; Vasatova, M.; Jebavy, L.; Zak, P. (Experimental Oncology, 2013)
Aim: Evaluation of serum levels of 17 cytokines and 5 adhesion molecules in patients with acute lymphoblastic leukemia (ALL) and in healthy subjects using biochip array technology. This approach allows multi-analytical determination from a single sample. Methods: A total of 15 ALL patients and 15 healthy subjects (blood donors) were studied. Serum samples were analyzed by biochip based immunoassays on the Evidence Investigator analyzer. T-tests were used for statistical analysis. Results: Comparing cytokine and adhesion molecule levels in ALL patients and in healthy subject, we found significant increase in serum VCAM-1 (p < 0.000001), ICAM-1 (p < 0.0001), L-selectin (p < 0.0001), IL-8 (p < 0.001), MCP-1 (p < 0.01), and significant decrease (p < 0.01) in serum IL-3 and IL-4. Conclusion: Our results indicate that serum levels of specific cytokines and adhesion molecules (VCAM-1, ICAM-1, L-selectin, IL-8, IL-3, IL-4, MCP-1) are significantly altered in patients with newly diagnosed ALL, reflecting activity of the disease. Further investigation is needed to establish if these alterations could be used as a prognostic indicator for ALL.